Cancer Chemotherapy in Clinical Practice - Priestman, Terrence (Springer London : Imprint: Springer, 2012)
The last decade has seen many dramatic changes in cancer chemotherapy, with the introduction of a number of new forms of treatment as well as important developments in the more traditional fields of cytotoxic and hormonal therapy. Now in its second edition, this book summarizes the whole range of systemic cancer therapies and their clinical applications, taking into account new drugs and the emerging concept of personalized therapy. Intended as an introductory text for junior doctors, nurses and medical students, Cancer Chemotherapy in Clinical Practice is divided into three sections: ·         The Theoretical Basis of Cancer Chemotherapy - following a historical introduction the different treatment modalities are explained in the context of basic tumor biology ·         Practical Aspects of Chemotherapy - covering dosing and drug delivery together with an extensive discussion of possible side-effects and their management ·         Chemotherapy in the Management of Cancer - explaining the place of drug treatment and the outcomes that can be expected from chemotherapy in all the major cancers Written in a consistent style, this book makes a wealth of complex information both readily accessible and easily understandable.